ANALISIS KECELAKAAN LALU LINTAS LUAR KOTA DITINJAU DARI KONDISI GEOMETRI JALAN - Pranata, Robi Irza; Fahmi, Khairul; Hidayat, Arifal (Jurnal Taxiway, 2019)
Researches in various districts or cities and even the State have identified a relationship between traffic conditions and accident rates, one of which is the rate of traffic accidents in the preceding visibility. Therefore, it is necessary to do further research on traffic accidents outside the city on road geometry as a reference in an effort to reduce the number of accidents. The purpose of this study is to know the characteristics of accidents that occur on road traffic, analyze accidents on roads caused by road geometry factors and evaluate the geometric shape of the road based on geometric specifications of the outer city according to PKJI 2014. The processing of the results of the acquisition data is aided by the application of autocad, one of which is to determine the shape of the cross section and the slope of the road in each STA as a reference for road type classification. Then recapitulate the number of traffic accidents that occurred in the last 5 years according to the time and location of the accident from the data from the Laka District of Kampar with the help of Microsoft Excel. From the results of the processed data, it can be concluded that the road geometry factors are caused by bumpy roads and hollow roads.